2016
DOI: 10.18632/oncotarget.11826
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the receptor tyrosine kinase RET in combination with aromatase inhibitors in ER positive breast cancer xenografts

Abstract: The majority of breast cancers are estrogen receptor positive (ER+). Blockade of estrogen biosynthesis by aromatase inhibitors (AIs) is the first-line endocrine therapy for post-menopausal women with ER+ breast cancers. However, AI resistance remains a major challenge. We have demonstrated previously that increased GDNF/ RET signaling in ER+ breast cancers promotes AI resistance. Here we investigated the efficacy of different small molecule RET kinase inhibitors, sunitinib, cabozantinib, NVP-BBT594 and NVP-AST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…GDNF is also able to increase VEGF-VEGFR interaction enhancing the migration of colon cancer cells [96]. In case of glioma or breast cancers, the GDNF-Ret signaling pathway can be blocked by GAS1 (growth arrest-specific 1) or by some Ret kinase inhibitors leading to the impairment of tumor growth [97,98]. GFLs are also linked with hepatocellular carcinoma (HCC), as high expression of GFRα3 or phosphorylation of Ret in HCC tissues and an increase of ARTN in the serum correlate with poor prognosis in HCC patients.…”
Section: In Cancersmentioning
confidence: 99%
“…GDNF is also able to increase VEGF-VEGFR interaction enhancing the migration of colon cancer cells [96]. In case of glioma or breast cancers, the GDNF-Ret signaling pathway can be blocked by GAS1 (growth arrest-specific 1) or by some Ret kinase inhibitors leading to the impairment of tumor growth [97,98]. GFLs are also linked with hepatocellular carcinoma (HCC), as high expression of GFRα3 or phosphorylation of Ret in HCC tissues and an increase of ARTN in the serum correlate with poor prognosis in HCC patients.…”
Section: In Cancersmentioning
confidence: 99%
“…Andreucci et al [109] (2016) demonstrated that a major cause of AI resistance is ligand-independent ER activation induced by activation of growth factor receptor(s) through PI3K/AKT/mTOR or MAPK [64,[118][119][120][121] . Thus, BC cells are able to escape the growth-control effect of endocrine drugs by increasing estrogen-independent ER activity [ Figure 3].…”
Section: Mechanisms Of Drug Resistance In Bcmentioning
confidence: 99%
“…Notably, RET expression appeared to increase in tumors with high residual proliferation and decreased in tumors gaining greater benefit from AI therapy. As noted above, RET has been linked with resistance to therapy and its potential as a therapeutic target has been suggested (37,38).…”
Section: Discussionmentioning
confidence: 99%